An astronaut's guide to life on earth - Hadfield, Chris. 1959- (Little, Brown and Company, 2013)
Colonel Chris Hadfield has spent decades training as an astronaut and has logged nearly 4000 hours in space. During this time he has broken into a Space Station with a Swiss army knife, disposed of a live snake while piloting a plane, and been temporarily blinded while clinging to the exterior of an orbiting spacecraft. Hadfield takes listeners deep into his years of training and space exploration to show how to make the impossible possible.